Perception of Teachers towards the Use of Instructional Materials in Teaching Mathematics at Secondary Level - Dawadi, Shiva Datta (Curriculum Development Journal, 2020)
The major objective of the study is to identify the perception of mathematics teachers towards the use of instructional materials in teaching mathematics for the students of secondary level and to compare their perceptions on the basis of their teaching experience. The study has adopted descriptive survey design. A set of the questionnaire with 24 statements regarding the use of instructional materials in teaching mathematics was the tool for collecting the data. The statements in the questionnaire were categorized into four categories as availability, appropriateness, self-confidence in using instructional materials, and motivation to use it. The questionnaire forms were distributed to 68 secondary school mathematics teachers of public schools. The data were collected, tabulated, ordered, compared, calculated and analyzed by using different statistical tools. Finally, it was found that teachers have negative attitudes towards the statements under the subheadings availability which indicates teachers do not feel comfortable in gathering the instructional materials in teaching mathematics and they were found to have positive towards the statements under the subheadings appropriateness, self-confidence in using, and motivation which means mathematics teachers are in the favor of appropriate use instructional materials in teaching mathematics, and they were found confident in using instructional materials. And also teachers are found motivated to use instructional materials in teaching mathematics at secondary level. The study also concluded that the perception of the teachers regarding the use of instructional materials in teaching mathematics at secondary level differs according to the teaching experience of the teachers. Interestingly, the teacher with less teaching experience were found more positive in using instructional materials in teaching mathematics at secondary level.